RENEWABLE ENERGY RESOURCE APPLICATION: SOLAR THERMAL COOLING SYSTEMS IN INDONESIA - Rahadiyanti, Melania (DIMENSI (Journal of Architecture and Built Environment), 2017)
The increasingly energy consumption needs for cooling space has caused utilization of solar thermal energy as a space cooler to become effort to decrease carbon emmision and air polution, and to save electricity power as well. This research aims to understand principle of solar thermal cooling system on building in Indonesia. This research uses literature review method by comparing some article from research journal about potencies and application of solar thermal cooling system on buildings in tropical country. The right utilization of solar thermal cooling system on building in Indonesia is solar thermal cooling system with open cycle with dust absorbent and humidity reduction.